Novel adipokines, high molecular weight adiponectin and resistin, are associated with outcomes following lower extremity revascularization with autogenous vein - Owens, Christopher D.; Kim, Ji Min; Hevelone, Nathanael D.; Hamdan, Allen; Raffetto, Joseph D.; Creager, Mark A.; Conte, Michael S. (Journal of vascular surgery, 2010)
A significant portion of patients undergoing lower extremity bypass surgery (LEB) for peripheral arterial disease (PAD) will have cardiovascular or graft-related events. It has been previously demonstrated that systemic inflammation is associated with PAD and its clinical outcomes. We hypothesized that serum biomarkers of insulin resistance and inflammation would identify a subgroup at elevated risk for graft failure, limb loss, and mortality. This was a prospective longitudinal study of patients (n = 225) undergoing LEB using autogenous vein. Baseline blood samples were obtained prior to surgery in the fasting state. High-sensitivity C-reactive protein (hsCRP) and the adipokines resistin and high-molecular weight adiponectin (HMWA) were measured by enzyme-linked immunosorbent assay (ELISA). Median follow-up was 893 days. The major endpoints of primary patency (PP) and amputation-free survival (AFS) were examined using multivariable methods. Endpoints were screened against biomarkers and patient characteristics for univariate associations. Promising explanatory variables ( P < .1) were included in multivariable Cox proportional hazard models. The mean age of subjects was 67.6 years; 71.6% were male and 87.1% were Caucasian. One hundred thirty-three (59.1%) subjects underwent bypass for critical limb ischemia (CLI) and 73 (32.4%) had tissue loss. Patients with CLI and diabetes demonstrated elevated resistin and hsCRP levels. HMWA levels correlated with CLI and with a measure of insulin resistance (HOMA-IR) but not with clinical diabetes. Baseline biomarkers were higher in those presenting with tissue loss and in patients with postoperative events (mortality, limb loss). After multivariable analysis (including CLI, diabetes, age, estimated glomerular filtration rate [eGFR], adiponectin, resistin, and CRP), resistin (hazard ratio [HR] 1.75, 95% confidence interval [CI], 1.07-2.85; P = .025) and CRP (HR 2.39, 95% CI, 1.30-4.39; P = .005) were independently predictive of reduced AFS. However, only resistin maintained its significance when restricted to the diabetic cohort (HR 2.10, 95% CI, 1.10-3.99; P = .025). Higher levels of HMWA were found to be associated with primary graft patency (HR 0.73 for graft failure; 95% CI, 0.55 to 0.97; P = .031) in a multivariable model adjusting for diabetes, CRP, African-American race, CLI, high-risk conduits, and redo bypass procedures. These findings suggest that serum biomarkers of insulin resistance and inflammation may be predictive of clinical outcomes following LEB. Improving the systemic milieu of insulin resistance and inflammation in these high-risk patients may lead to reduced morbidity and mortality.